Prevalence of sports injuries and chronic pain in athletes practising kickboxing and taekwondo - Boguszewski, D.; Adamczyk, J.; Obszynska-Litwiniec, A.; Korabiewska, I.; Dabek, A.; Bialoszewski, D. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: Bodily injuries and pain conditions are the primary negative aspects related to practising combat sports. The study aimed to characterise the bodily injuries and chronic pain conditions experienced by men practising kickboxing and taekwondo.